2009
DOI: 10.1371/journal.pone.0006229
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cancer with Serum miRNAs on an Oligonucleotide Microarray

Abstract: Micro RNAs (miRNAs) are a class of small, non-coding RNA species that play critical roles throughout cellular development and regulation. miRNA expression patterns taken from various tissue types often point to the cellular lineage of an individual tissue type, thereby being a more invariant hallmark of tissue type. Recent work has shown that these miRNA expression patterns can be used to classify tumor cells, and that this classification can be more accurate than the classification achieved by using messenger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
256
0
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(276 citation statements)
references
References 50 publications
10
256
0
9
Order By: Relevance
“…13 Detectable levels of free miRNAs were recently found to exist in serum, 14 and subsequent studies have shown that circulating miRNAs can be useful markers of cancer. [15][16][17] In prostate cancer, the level of a number of miRNAs is altered in the serum of men with advanced disease and these markers can be used to discriminate cancer patients from healthy individuals. 11,[17][18][19] Moreover, two recent reports found that some circulating prostate cancer-associated miRNAs correlate with risk of disease progression 20 and other predictors of disease outcome, such as Gleason score and lymph-node status, 18 highlighting the prognostic potential of this class of molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Detectable levels of free miRNAs were recently found to exist in serum, 14 and subsequent studies have shown that circulating miRNAs can be useful markers of cancer. [15][16][17] In prostate cancer, the level of a number of miRNAs is altered in the serum of men with advanced disease and these markers can be used to discriminate cancer patients from healthy individuals. 11,[17][18][19] Moreover, two recent reports found that some circulating prostate cancer-associated miRNAs correlate with risk of disease progression 20 and other predictors of disease outcome, such as Gleason score and lymph-node status, 18 highlighting the prognostic potential of this class of molecules.…”
mentioning
confidence: 99%
“…[15][16][17] In prostate cancer, the level of a number of miRNAs is altered in the serum of men with advanced disease and these markers can be used to discriminate cancer patients from healthy individuals. 11,[17][18][19] Moreover, two recent reports found that some circulating prostate cancer-associated miRNAs correlate with risk of disease progression 20 and other predictors of disease outcome, such as Gleason score and lymph-node status, 18 highlighting the prognostic potential of this class of molecules. However, the clinical utility of these miRNAs is yet to be validated in larger cohorts, and more comprehensive analyses to identify other circulating miRNAs associated with prostate cancer are needed.…”
mentioning
confidence: 99%
“…MiRNAs have identified deregulated in plasma and serum microvesicles in prostate cancer patients compared with healthy control [64] and were also associated with the stage of the disease, the Gleason score and lymph node metastasis. For instance, Lodes et al found 15 miRNAs (miR-16, -92a, -103, -107, -197, -34b, -328, -485-3p, -486-5p, -92b, -574-3p, -636, -640, -766, -885-5p) overexpressed in serum from stage 3 and 4 prostate cancer patients compared with healthy controls [65]. Furthermore, Mahn et al, found miR-26a, miR-195, and let-7i to be up-regulated in patients with prostate cancer compared with patients affected by benign prostatic hyperplasia [66].…”
Section: Exosomes and Prostasomesmentioning
confidence: 99%
“…Moreover, miR-141 was correlated with serum PSA levels and could detect individuals with advanced PCa with 60% sensitivity at 100% specificity. A subsequent study used a custom microarray to profile miRNAs in serum from patients with various cancer types and identified 15 miRNAs at elevated levels in the circulation of PCa patients (Lodes et al 2009). However, only six PCa samples from men with significant disparities, including age, disease grades, and modes of treatment, were analyzed.…”
Section: Circulating Mirnas As Diagnostic Markers Of Pcamentioning
confidence: 99%